Tunisia : Financial Sector Assessment Program Update; Detailed Assessment of Compliance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Detailed Assessment of Compliance of the Basel Core Principles for Effective Banking Supervision for Tunisia. The findings reveal that the Central Bank of Tunisia (Banque Centrale de Tunisi/BCT) monitors closely the supervised institutions. Its monitoring consists of examining prudential reports and the numerous documents that the external auditors of the credit institutions have to submit at the close of each year, extracting information from inspection reports. Direction Generale de Supervision Bancaire (DGSB) staff are trained in economics, accounting, and finance.